American Experimental Music 1890-1940 - Nicholls, David (Cambridge Cambridge University Press, 1991)
From the end of the nineteenth century a national musical consciousness gradually emerged in the United States as composers began to turn away from the European conventions on which their music had been modeled. It was in this period of change that experimentalism was born and America subsequently became, as it still is, a major source of new musical ideas for European musicians. David Nicholls considers the most influential figures in the development of American experimentalism, including Charles Ives, Charles Seeger, Ruth Crawford, Henry Cowell and the young John Cage. He analyzes the music and ideas of this group, explaining the compositional techniques invented and employed by them and the historical and cultural context in which they emerged. The book is thus an important contribution toward our understanding of some of the most challenging music of the twentieth century.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music history; Avant-garde; USA